The Community Empowerment Through Social and Educational Institutions - Bayu Adi Laksono (Jurnal Pendidikan Humaniora, 2018)
Abstract: The purpose of this study is to explore the role of social and educational institutions in Bajulmati in the process of community empowerment. This research uses a qualitative approach. The informants in this study consisted of government institutions, empowerment activists from social and educational institutions, and the surrounding community. The results of the study show the role of social and educational institutions in empowering Bajulmati people. Communities are empowered through the utilization of natural and human resources, to always be optimistic and independent, and empowered through school education institutions aimed at increasing competitiveness, education outside the school system to maintain the culture and noble values of Bajulmati people.Key Words: community empowerment, education, economy, social Abstrak: Tujuan dari penelitian ini adalah menggali peran lembaga sosial dan pendidikan di Bajulmati dalam proses pemberdayaan masyarakat. Penelitian ini menggunakan pendekatan kualitatif. Informan dalam penelitian ini terdiri dari institusi pemerintahan, pegiat pemberdayaan dari lembaga sosial dan pendidikan, serta masyarakat sekitar. Hasil penelitian menunjukkan peran lembaga sosial dan pendidikan dalam memberdayakan masyarakat Bajulmati. Masyarakat diberdayakan melalui pemanfaatan potensi alam maupun sumber daya manusia, untuk selalu bersikap optimis dan mandiri, serta diberdayakan melalui institusi pendidikan pendidikan persekolahan bertujuan untuk meningkatkan daya saing, pendidikan di luar sistem persekolahan untuk menjaga budaya dan nilai-nilai luhur masyarakat Bajulmati.Kata kunci: pemberdayaan masyarakat, pendidikan, ekonomi, sosial